Exploring regional domains: a comparative history of regionalism - Fawcett, L (Blackwell Publishing Ltd, 2004)
This article offers an overview of the history and development of regionalism with a view to providing a framework for thinking about its progress and prospects in different parts of the world. After a preliminary discussion of the problems encountered in defining regions and regionalism, the article moves to a historical and comparative analysis, ranging widely to include examples from many different regions. It argues that regionalism should be understood as an evolutionary and cumulative process, which has grown and expanded to take in new tasks and new domains. It has become an increasingly important component of the different structures of global governance, and one whose potential neither states, multilateral institutions, nor non-state actors can afford to ignore.